Ecological Impacts and Management of Nasutitermes matangensis Infestation on Jabon (Anthocephalus cadamba) in a Grand Forest Park Landscape (Aceh Besar, Sumatra): Nasutitermes matangensis Infestation on Jabon in Aceh Besar Grand Forest Park - Nirma Febrika; Essy Harnelly; Samingan Samingan; Novita Novita; Mohammad Adzannie Bessania; Syaukani Syaukani (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The rising demand for fast-growing timber species such as Anthocephalus cadamba has driven the expansion of monoculture plantations across Southeast Asia. While these systems support rapid biomass production and reforestation, their simplified structure can reduce ecological resistance and increase susceptibility to insect pests. Among these, arboreal termites of the genus Nasutitermes, particularly N. matangensis, have recently been reported attacking young A. cadamba plantations in Indonesia. This study examined infestation patterns, damage intensity, and ecological drivers of N. matangensis in A. cadamba stands at Pocut Meurah Intan Grand Forest Park, Aceh Besar, Sumatra. Field surveys of 150 trees across 10 plots revealed that 42% were infested by termites, with 26% suffering moderate-to-severe damage, including bark degradation, stem girdling, and canopy dieback. Infestation was significantly higher in shaded, poorly managed plots characterised by dense understory vegetation, high humidity, and woody debris accumulation. Trees with mechanical injuries or fungal infections were more prone to colonisation. These findings highlight that termite infestation is strongly influenced by plantation structure, host condition, and microclimatic factors. Although N. matangensis plays an important ecological role as a decomposer, its opportunistic behaviour in stressed plantation systems can lead to substantial productivity losses. An integrated pest management (IPM) approach—combining improved silvicultural practices, habitat sanitation, early detection, and biological control—is recommended to mitigate termite impacts and support sustainable plantation management